Necessidades de pessoas com Transtorno de Déficit de Atenção e Hiperatividade: análise psicológicapara desenvolvimento de jogo com tecnologia Kinect - Rebecca Nunes de Assis (Universidade Federal do Amazonas, 2016)
Attention Deficit Hyperativity Disorder is formed by an inappropriate level of attention, impulsivity or hyperactivity, producing functional impairment in daily life of a person. Those symptoms appear approximately at seven years old, evidenciated by the start of school activities. Recognizing the importance of playful actions in the juvenile care, we aimed to analyze what people with ADHD needs, whose may contribute to the development of a game with Kinect technology. For this, we sought to understand the difficulties resulting from this disorder, identify and propose some behaviors and contexts that, when stimulated through a game with Kinect technology, operating as adjunctive therapy in attendance. We conducted literature survey on the topic, including interviews and articles published on the Internet, focusing, including evidence of the potential to be worked. It was observed that the Kinect, efficient in capturing global body movements, technology is able to stimulate the space-time concept and attention, in addition to providing a self-reflection and learning new behaviors from the plot of the game. A clientele seeking 08-11 year old with a diagnosis of ADHD, as indicated prior proposal to use a regional setting, in order to acclimatise the players in context of familiarity and curiosity.